Health Leadership and Management Development in Malawi: Towards a Theory for Health Systems Strengthening - O'Byrne, Thomasena (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2022)
Background: Strong leadership and management capacity of Human Resources for Health (HRH) is key to a health system s performance. However, there is a dearth of evidence-based literature on the application of health leadership and management development for health systems strengthening (HSS) in low- and middle-income contexts (LMICs), particularly those with decentralised governments. The current study sought to develop a framework for how health leadership and management is understood, further developed, and applied for HSS in Malawi, placing HRH at the centre of efforts. Methods:The study was informed by a qualitative case study methodology, drawing on the concepts and tools of grounded theory approaches, and using a soft-systems thinking lens. Four key methods were utilised, across a broad range of health-system stakeholders, including a documentary review of over 200 documents; in-depth interviews (n = 37); non-participant observation; and the development of rich pictures through systems mapping. Stakeholders included healthcare workers, researchers, implementers, development partners and policy makers.Results:Principal findings from the study suggest a range of efforts and investment in Malawi to develop health leadership and management. However, the health landscape was awash with partners, with competing priorities often focused on individual programmes and agendas rather than the health system. Insights into values frontline stakeholders attach to effective leadership and management evidence a desire for approaches that are more relational and collectivistic, situated within a more psychologically safe and supportive working environment. There was a stark contrast between what stakeholders assumed to be happening and the lived experiences of those intended to benefit from leadership and management interventions such as the health workforce. With much of the focus being directed at district level, already overburdened district health management teams faced unrealistic expectations as health leaders and managers. There was an identified desire for efforts to focus on developing health leadership and management at all levels of the health system, leveraging existing, yet often ignored, strengths and resilience at primary and community health care level. Discussion/Conclusion:The theoretical model developed from this study depicts how empowering collective leadership across all HRH at all levels of a health system can lead to a stronger health system, improved health and well-being, and more satisfied staff, patients, and communities. For leadership and management development to contribute to HSS, it must be aligned to the principles of systems thinking and applied faithfully system wide to enable people to better cope with their contexts.
APPROVED
Keywords: Collective Leadership; Decentralisation; Health Leadership and Management Development; Health Systems Strengthening; Human Resources for Health; Malawi; Primary Health Care; Soft Systems Thinking